Rain Variability in Arid Regions and Its Impact on the Environment: Al-Kufra as a Model (Journal of human and social sciences, 2025)
Al‑Kufra is classified as one of the geographical regions characterized by an arid climate, marked by extremely low rainfall. However, it has recently experienced repeated precipitation events resulting from the passage of trade winds during summer, as well as clouds forming over the northwestern coast and moving toward the northeastern coast, allowing some cloud masses to drift into the southeastern part of the country.             Based on this, rainfall in the study area was analyzed over a period exceeding 90 years (1933–2025). The data were divided into three climatic periods and examined as hydrological years to identify rainfall and drought patterns, as well as the potential temporal windows for precipitation in the specified geographic location, measured in millimeters. With the beginning of the first recorded measurements at the Al‑Kufra meteorological station in 1933, the distribution of rainfall across the seasons became evident, with winter showing the highest frequency—exceeding one‑third of the total recorded events. However, frequency does not necessarily reflect the total accumulated amount. For instance, in August of the summer of 2023–2024, the highest daily rainfall was recorded at 56 mm in a single day. Total rainfall during 2023–2024 increased to 86.3 mm, nearly double the long‑term average, indicating clear signs of ongoing climatic changes that have affected the region’s climate, particularly rainfall, which in turn has had significant biological impacts.This study addressed numerous questions using satellite imagery, maps, rainfall charts, cloud‑movement tracking, and precipitation data analysis. There is little doubt that rainfall readings could increase substantially if additional measurement stations were installed along the southern belt of the country, which would enhance the accuracy of local forecasting, reduce potential risks, and potentially alter the rainfall‑based classification of arid desert environments.
Keywords: Arid Regions; Rainfall Precipitation; Environmental Impacts; Rain and Drought Cycles; Biodiversity